MANAGEMENT SYSTEM OF MASTER’S STUDY PROGRAM OF ENGLISH LANGUAGE EDUCATION, TEACHER TRAINING AND EDUCATION FACULTY, TANJUNGPURA UNIVERSITY - Sudarsono Sudarsono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
A study program is qualified excellent if its management system is excellent. The present study was designed to examine the management system applied in Master’s Study Program of English Language Education (S2BE). The respondents were students, alumni, alumni users, and lecturersof S2BE. Totally, they were 136 people. The data were collected indirectly through with a questionnaire as an instrument. The data were analyzed in a very simple qualitative, statistical work. The research found out that the respondents qualified their agreement to the statements in the questionnaire concerning personnel management, leadership, governance, and quality assurance ranging from ‘S’ (agree) to ‘S++’ (stronglyagree). Most respondents chose‘S++’